Cytogenetic and molecular mechanisms of chronic myelogenous leukemia - Özbey, Ülkü; Yüce, Hüseyin (My University, 2007)
Chronic myeloid leukemia (CML) is characterized by the Philadelphia (Ph) chromosome in about % 95 of patients, resulting from the translocation t(9;22)(q34;q11.2). This translocation leads to the formation of the chimeric BCR/ABL gene on the Ph chromosome. CML has a typical progressive course with transition from a chronic phase (CP) to terminal blastic phase (BP). The mechanisms of action leading to disease progression are still poorly understood. Secondary chromosomal abnormalities, +8 (34% of cases with additional changes), +Ph (30%), i(17q) (20%), +19 (13%), - Y (8% of males), +21 (7%), +17 (5%), and monosomy 7 (5%) for example, are well known to be associated with disease progression. Disease progression and BC CML is associated with characteristic non-random cytogenetic and molecular events. These can be viewed as increased oncogenic activity or loss of tumor suppressor activity. What causes transformation and disease progression to blast crisis is only poorly understood. In vitro and in vivo studies will be needed to provide a complete understanding of the contribution of BCR-ABL and other genes to disease progression. Despite extensive cytogenetic and molecular investigations, the mechanisms underlying the formation of the Ph and the pathogenesis of Ph positive CML are still unknown but are now the object of intensive research.
Kronik miyeloid löseminin sitogenetik ve moleküler mekanizmasi
Keywords: BCR ABL protein; chromosome aberration; chromosome analysis; chromosome translocation; chronic myeloid leukemia; disease course; genetic analysis; human; monosomy; Philadelphia 1 chromosome; review